Endothelial TFEB (Transcription Factor EB) Positively Regulates Postischemic Angiogenesis. Issue 7 (30th March 2018) - Fan, Yanbo; Lu, Haocheng; Liang, Wenying; Garcia-Barrio, Minerva T.; Guo, Yanhong; Zhang, Ji; Zhu, Tianqing; Hao, Yibai; Zhang, Jifeng; Chen, Y. Eugene
Abstract : Rationale: : Postischemic angiogenesis is critical to limit the ischemic tissue damage and improve the blood flow recovery. The regulation and the underlying molecular mechanisms of postischemic angiogenesis are not fully unraveled. TFEB (transcription factor EB) is emerging as a master gene for autophagy and lysosome biogenesis. However, the role of TFEB in vascular disease is less understood. Objective: : We aimed to determine the role of endothelial TFEB in postischemic angiogenesis and its underlying molecular mechanism. Methods and Results: : In primary human endothelial cells (ECs), serum starvation induced TFEB nuclear translocation. VEGF (vascular endothelial growth factor) increased TFEB expression level and nuclear translocation. Utilizing genetically engineered EC-specific TFEB transgenic and KO (knockout) mice, we investigated the role of TFEB in postischemic angiogenesis in the mouse hindlimb ischemia model. We observed improved blood perfusion and increased capillary density in the EC-specific TFEB transgenic mice compared with the wild-type littermates. Furthermore, blood flow recovery was attenuated in EC-TFEB KO mice compared with control mice. In aortic ring cultures, the TFEB transgene significantly increased vessel sprouting, whereas TFEB deficiency impaired the vessel sprouting. In vitro, adenovirus-mediated TFEB overexpression promoted EC tube formation, migration, and survival, whereas siRNA-mediated TFEB knockdown had the opposite effect. Mechanistically, TFEB activated AMPK (AMP-activated protein kinase)-α signaling and upregulated autophagy. Through inactivation of AMPKα or inhibition of autophagy, we demonstrated that the AMPKα and autophagy are necessary for TFEB to regulate angiogenesis in ECs. Finally, the positive effect of TFEB on AMPKα activation and EC tube formation was mediated by TFEB-dependent transcriptional upregulation of MCOLN1 (mucolipin-1). Conclusions: : In summary, our data demonstrate that TFEB is a positive regulator of angiogenesis through activation of AMPKα and autophagy, suggesting that TFEB constitutes a novel molecular target for ischemic vascular disease. Abstract : Supplemental Digital Content is available in the text.